2020
DOI: 10.1155/2020/4587148
|View full text |Cite
|
Sign up to set email alerts
|

A New Endophytic Fusarium Oxysporum Gibberellic Acid: Optimization of Production Using Combined Strategies of Experimental Designs and Potency on Tomato Growth under Stress Condition

Abstract: This study reports the potential of the endophytic fungi identified as a Fusarium oxysporum to produce gibberellic acid (GA3). The GA3 production was confirmed by high performance liquid chromatography. To improve the production of this phytohormone under solid state fermentation (SSF), successive optimization strategies were used. Firstly, Plackett-Burman design was applied for screening medium components and culture condition. Under the optimized condition, GA3 yield (7.14 g/kg) was 2.62-fold higher than by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 42 publications
1
18
0
1
Order By: Relevance
“…The role of gibberellic acid (GA) in conferring sugar‐mediated drought stress tolerance has been documented, for example, GA is involved in augmenting the sucrose and dry matter content in sugarcane (Rai et al, 2017). Further, external application of 10 mM of gibberellic acid on tomato was shown to enhance sugar and proline content, which function as osmoprotectants and help in improve plant growth characteristics under salt mediated osmotic stress conditions (Ben Rhouma et al, 2020).…”
Section: Sugars Network With Phytohormones To Mediate the Drought Stress Responsementioning
confidence: 99%
“…The role of gibberellic acid (GA) in conferring sugar‐mediated drought stress tolerance has been documented, for example, GA is involved in augmenting the sucrose and dry matter content in sugarcane (Rai et al, 2017). Further, external application of 10 mM of gibberellic acid on tomato was shown to enhance sugar and proline content, which function as osmoprotectants and help in improve plant growth characteristics under salt mediated osmotic stress conditions (Ben Rhouma et al, 2020).…”
Section: Sugars Network With Phytohormones To Mediate the Drought Stress Responsementioning
confidence: 99%
“…Indeed, the key parameters such as pH, agitation, airflow, dissolved oxygen, temperature, and feeding pumps were affected by large-scale production of microbial mass production [16,18]. Many studies have been reported to evaluate the cultivation parameters for Trichoderma sp., by using a submerged fermentation system to increase its bioactive metabolites as well as conidia [14][15][16][17]. To detect perfect conditions for transposing the cultivation of endophytic T. harzianum to the industrial scale, the batch and exponential fedbatch fermentation modes were applied in our work.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the tested microbial cells must survive multiple processing stages without destroying their quality and quantity [14]. Therefore, there are low-cost materials such as agro-wastes that have been utilized as carbon and nitrogen sources for culturing microbial cells to reduce production line costs [14][15][16][17]. For the commercial scale-up approach, two distinct fermentation systems called solid-state and submerged fermentation were applied accordingly to the sensitivity of microbial cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many commercially important products have been produced by SSF using cow dung ( Vijayaraghavan et al, 2016 ). Recently, gibberellic acid production has been optimized for Fusarium oxysporum using various optimization strategies and the potency was evaluated under stress condition ( Ben Rhouma et al, 2020 ). The application of gibberellic acid and advances were recently reported by de Camara et al (2018) .…”
Section: Introductionmentioning
confidence: 99%